PENERAPAN SANKSI PENYALAHGUNAAN NARKOTIKA DITINJAU DARI SURAT EDARAN MAHKAMAH AGUNG NOMOR 4 TAHUN 2010 TENTANG PENEMPATAN KORBAN PENYALAHGUNAAN DAN PECANDU NARKOTIKA KE DALAM LEMBAGA REHABILITASI MEDIS DAN REHABILITASI SOSIAL (STUDI PUTUSAN NOMOR 56/PID.SUS/2019/PN/SDA) - Chrysto Fransco Siletty; R. Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2021)
The State of Indonesia is one of the countries with the concept of the Supremacy of Law, namely the law is above all, the law is used as the superiority of the rules of the game in a country or can be called a state of law (rechtsstaat). Therefore, Indonesia is a legal state that obeys the rules contained in the laws and regulations that apply in Indonesia. Law is an absolute thing owned by a country regardless of the system used by the country, as stated in Article 1 Paragraph (3) of the 1945 Constitution of the Unitary State of the Republic of Indonesia stating that the Indonesian State is based on law, not based on mere power. Based on the contents of this thesis, there are problems, namely How to Implement Rehabilitation Sanctions for Narcotics Criminals in Indonesia Judging from Law Number 35 of 2009 in conjunction with the Circular Letter of the Supreme Court Number 4 of 2010 Rehabilitation Sanctions for Indonesian Narcotics Crime Perpetrators Judging from Law Number 35 of 2009 in conjunction with the Circular Letter of the Supreme Court Number 4 of 2010. Based on the research data as follows: That he is the defendant ARDIANSAH BIN Alm. ARIFUDDIN, on Monday 05 November 2018 at around 23.00 WIB or at least in November 2018 or at least sometime in 2018.